2016
DOI: 10.1371/journal.pntd.0004308
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Manipulation of Leishmania donovani to Explore the Involvement of Argininosuccinate Synthase in Oxidative Stress Management

Abstract: Reactive oxygen and nitrogen species (ROS and RNS) produced by the phagocytic cells are the most common arsenals used to kill the intracellular pathogens. However, Leishmania, an intracellular pathogen, has evolved mechanisms to survive by counterbalancing the toxic oxygen metabolites produced during infection. Polyamines, the major contributor in this anti-oxidant machinery, are largely dependent on the availability of L-arginine in the intracellular milieu. Argininosuccinate synthase (ASS) plays an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Terbinafine resistance locus protein has previously been identified to mediate efflux of terbinafine in L. major [ 32 ] and argininosuccinate synthase gene has been identified to be associated with antimony resistance in L. infantum [ 33 ]. Also an up regulation of argininosuccinate synthase gene was seen in Leishmania parasites as a response to oxidative stress and arginine starvation and the viability of the parasites were seen to notably reduce when the gene was down regulated, indicating an important role of the argininosuccinate synthase gene in infectivity and survival of the parasites in the mammalian host [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Terbinafine resistance locus protein has previously been identified to mediate efflux of terbinafine in L. major [ 32 ] and argininosuccinate synthase gene has been identified to be associated with antimony resistance in L. infantum [ 33 ]. Also an up regulation of argininosuccinate synthase gene was seen in Leishmania parasites as a response to oxidative stress and arginine starvation and the viability of the parasites were seen to notably reduce when the gene was down regulated, indicating an important role of the argininosuccinate synthase gene in infectivity and survival of the parasites in the mammalian host [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In ISC1 versus CG we detected a higher concentration of citrulline and a lower concentration of argininosuccinate. In organisms with a complete urea cycle, argininosuccinate is then further converted to arginine and fumarate by argininosuccinate lyase (ASL), however, in Leishmania this enzyme is missing ( Sardar et al, 2016 ). This difference is of particular interest since both argininosuccinate and arginine deprivation have been linked with reduced thiol content ( Sardar et al, 2016 ; Mandal et al, 2016 ) and ASS mutants have shown a lower virulence than WT parasites ( Lakhal-Naouar et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, ASS activity converting citrulline to arginosuccinate has been demonstrated. It seems that ASS activity is not related with L -arginine synthesis, but with important biological functions of arginosuccinate in the establishment of the infection ( Lakhal-Naouar et al, 2012 ; Sardar et al, 2016 ).…”
Section: Leishmania L -Arginine Metabolismmentioning
confidence: 99%